2018
DOI: 10.17844/jphpi.v20i3.19768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extraction Methods on Characteristic of SodiumAlginate from Brown Seaweed Sargassum fluitans

Abstract: AbstrakAlginat merupakan metabolit primer yang banyak dibutuhkan industri pangan maupun nonpangan. Metode ekstraksi alginat dari rumput laut berpengaruh pada viskositas dan rendemen yang dihasilkan. Penelitian ini bertujuan untuk mengetahui pengaruh metode ekstraksi terhadap karakteristik dan kualitas natrium alginat Sargassum fluitans serta biaya ekstraksi yang diperlukan. Penelitian ini menggunakan dua metode ekstraksi yang berbeda yaitu metode ekstraksi asam dan kalsium. Parameter kualitas yang dilakukan pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
(6 reference statements)
0
10
1
Order By: Relevance
“…Sodium alginate has three specific peaks: hydroxyl bonds in the absorption area of about 3500 cm -1 , COO-asymmetrical in the absorption area of about 1620 cm -1 , and COO-symmetrical in the absorption area of about 1410 cm -1 . At the same time, alginate fingerprints will be present at a wavelength of 950-750 cm -1 [3,8,14,15]. Therefore, the current FTIR analytical study shows that the alginate spectrum corresponded to a positive reference and fingerprint at a specific alginate wavenumber.…”
Section: Ftir Analysismentioning
confidence: 66%
“…Sodium alginate has three specific peaks: hydroxyl bonds in the absorption area of about 3500 cm -1 , COO-asymmetrical in the absorption area of about 1620 cm -1 , and COO-symmetrical in the absorption area of about 1410 cm -1 . At the same time, alginate fingerprints will be present at a wavelength of 950-750 cm -1 [3,8,14,15]. Therefore, the current FTIR analytical study shows that the alginate spectrum corresponded to a positive reference and fingerprint at a specific alginate wavenumber.…”
Section: Ftir Analysismentioning
confidence: 66%
“…38 The peaks at 1614 and 1414 cm −1 prove the presence of the O−C−O asymmetric stretching vibration and O−C−O symmetric stretching vibration, which are the characteristic peaks of SA. 39 The CS peaks appear at 3449 (O−H and N−H stretch), 2922 (C−H stretch), 1614 (−NH 2 bend), 1422 (CH 2 bend), 1383 (CH 3 symmetrical deformation), 1327 (C− N stretch), and 1059 cm −1 (C−O stretch). 40 The peak around 1614 cm −1 proves the presence of bending vibrations of the amine group (−NH 2 ), which is the characteristic peak of CS.…”
Section: Sem Imagesmentioning
confidence: 99%
“…There could still be many impurities in the alginate solution, which would raise the ash content of the extracted alginate [32]. [45] reported that factors affecting the ash content of alginate included habitat and water conditions, mineral content in seaweed, and post-harvest handling. [1] and [45] informed that the high ash content of the extracted alginate is probably due to the presence of NaCl salt residue that is not removed when washing the alginic acid precipitate so that it does not dissolve when it is deposited using isopropyl alcohol.…”
Section: Ash Contentmentioning
confidence: 99%